Investigating the Source and Strategies Adopted by Mainstream Media in Combating Fake News in the Kingdom of Eswatini. Issue 4 (2nd October 2019) - Lunga, Carolyne Mande; Mthembu, Maxwell Vusumuzi
ABSTRACT: The spread of "fake news" is a threat to the credibility of the media in the Southern African Development Community (SADC), including Eswatini (formerly Swaziland). These intentionally false stories or disinformation purporting to be news threaten the democratic role of mainstream media in creating a well-informed citizenry. There is hate speech, and disinformation directed at the royal family, the cabinet, prominent figures and the larger Swazi society. This study focuses on disinformation in the mainstream media, the Swazi Observer and the Times of Swaziland, and the strategies being adopted to combat it. The article adopts a qualitative methodological approach using in-depth interviews with journalists and qualitative content analysis of the newspapers as data-gathering methods. The study reveals that the dissemination of false information is partially a consequence of the secretive nature of Swazi society even on matters of public interest. This has resulted in people spreading false news through social media aimed at ridiculing those in authority. On the other hand, "fake news" has found its way into mainstream media as journalists use the internet and social media such as Facebook and Twitter as sources of news without verifying their authenticity due to the pressure to be the first to publish.